1991
DOI: 10.1038/bjc.1991.133
|View full text |Cite
|
Sign up to set email alerts
|

High frequency mutation in codons 12 and 61 of H-ras oncogene in chewing tobacco-related human oral carcinoma in India

Abstract: Summary 57 primary tumour samples from Indian oral cancer patients with a 5-15 year tobacco chewing habit, were examined for mutational activation in codons 12, 13 and 61 of the H-ras, K-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
120
4
1

Year Published

1993
1993
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(132 citation statements)
references
References 26 publications
6
120
4
1
Order By: Relevance
“…Previous studies have identified a number of genetic abnormalities in HNSCC, including nonrandom cytogenetic aberrations (Cowan et al, 1992;Heo et al, 1989), mutation or overexpression of the H-ras gene (Saranath et al, 1991) and p53 gene (Brennan et al, 1995;Field et al, 1992), and overexpression of epidermal growth factor receptor (Grandis et al, 1998a(Grandis et al, , 1998b. Inactivation of p16 gene (CDKN2), a G1 cyclindependent kinase inhibitor and DCC (deletion in colon cancer) gene, has also been reported (Reed et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have identified a number of genetic abnormalities in HNSCC, including nonrandom cytogenetic aberrations (Cowan et al, 1992;Heo et al, 1989), mutation or overexpression of the H-ras gene (Saranath et al, 1991) and p53 gene (Brennan et al, 1995;Field et al, 1992), and overexpression of epidermal growth factor receptor (Grandis et al, 1998a(Grandis et al, , 1998b. Inactivation of p16 gene (CDKN2), a G1 cyclindependent kinase inhibitor and DCC (deletion in colon cancer) gene, has also been reported (Reed et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, despite the great emphasis on early detection and the efforts to improve multimodality treatment management, 5-year survival rate for HNSCC patients does not exceed 50% (Ries et al, 1990). The pressing epidemiologic problem and the lack of effective management for patients with HNSCC thus strengthen the need for more extensive research on HNSCC at the molecular and genetic levels.Previous studies have identified a number of genetic abnormalities in HNSCC, including nonrandom cytogenetic aberrations (Cowan et al, 1992;Heo et al, 1989), mutation or overexpression of the H-ras gene (Saranath et al, 1991) and p53 gene (Brennan et al, 1995;Field et al, 1992), and overexpression of epidermal growth factor receptor (Grandis et al, 1998a(Grandis et al, , 1998b. Inactivation of p16 gene (CDKN2), a G1 cyclindependent kinase inhibitor and DCC (deletion in colon cancer) gene, has also been reported (Reed et al, 1996).…”
mentioning
confidence: 99%
“…In the Western world, ras mutations in SCCHN are very rare (< 5%), whereas in India 35% of SCCHN patients harbour a mutation in H-ras, and this has been associated with tobacco chewing (Saranath et al, 1991). In Taiwan, 18% of oral cancer patients investigted were found to have a K-ras mutation, and these patients chew betel quid but do not use tobacco (Kuo et al, 1994).…”
Section: Redsmentioning
confidence: 99%
“…Loss of heterozygosity (LOH) of the H-ras locus has been reported in a number of carcinomas (Shiraishi et al, 1987;Garcia et al, 1989;Vachtenheim et al, 1994), including SCCHN (Howell et al, 1989;Sheng et al, 1990;Kiaris et al, 1994), and it has been proposed that the normal H-ras gene may possess tumour-suppressor as well as oncogene functions . Recently, we reported that genetic instability of a repetitive element which is located within intron 1 of H-ras is associated with the nodal status of patients with SCCHN (Saranath et al, 1991) and is most likely to be associated with the chewing of tobacco. Although ras mutations are considered to be rare events in the Western world (Field, 1992, for a review), overexpression of ras family genes has been reported by a number of investigators.…”
mentioning
confidence: 99%
“…Mutant ras is also found in high proportions of carcinogen-induced cancers including lung and bladder cancers (Mirvish, 1995). Although ras mutations have been reported in 35% of oral cancers in India and Southeast Asia where betel nut chewing and reverse smoking are prevalent, ras mutations in oral cancers are quite rare in patients in the Western Hemisphere (Clark et al, 1993;Saranath et al, 1991;Jordan and Daley, 1997). It is thus likely that activation of other ras-like proteins may play a role in oral carcinogenesis because SMGs are integral members of the growth factor signaling pathways (Bokoch, 1993).…”
Section: Introductionmentioning
confidence: 99%